How can intergenerational learning with ICT help to strengthen intergenerational solidarity? - Patrício, Maria Raquel (2012)
The participation of older adults in the Information and Knowledge Society implies the need to strengthen the improvement of their skills, particularly in the context of Information and Communication Technology (ICT). We believe that if younger generations are involved in this process of learning supported by ICT, in an intergenerational perspective of development, the inclusion of older people in society will be reinforced and will promote active ageing, also fighting loneliness social exclusion. Therefore, the following research question was formulated: how can intergenerational learning with ICT help to strengthen intergenerational solidarity? This paper presents a learning project involving different generations in activities supported by ICT, focusing in older people and volunteer higher education students. The project aims to promote intergenerational learning through ICT; cooperation between youth and seniors in the digital skills, sharing experiences and knowledge; and contribute to digital inclusion and participation of the senior population in the community and knowledge society. The intergenerational workshops run in a non-formal learning environment, in order to respond to technological needs and interests of seniors. This article reports on the findings of a qualitative study, in which surveys, focus groups, informal interviews and observation were used to explore learning needs and experiences, and how intergenerational learning with ICT happened. The findings suggest that intergenerational learning promote a dialogue, interaction and mutual cooperation between different generations.